On Generalized Derivations Of Jordon Algebras (Texas Journal of Engineering and Technology, 2022)
In the present article the concept of generalized derivations of Jordan algebras is introduced and the general properties of generalized derivations are studied. In particular, invariants are constructed in Jordan algebras using generalized derivations. Also, a description, for some values of the parameters a, b, g, of the sets of all (a, b, g) -derivations of Jordan algebrasis given.